Adequacy of mathematical models for calculating the diffusion coefficient of gasoline - Бойченко, С. В.; Федорович, Л. А.; Тітова, О. С. (Proceedings of National Aviation University, 2002)
The mathematical models of determination of gasoline diffusion coefficient are analyzed, the comparative characteristic of known methods is compiled and their adequacy is determined by experimental data.